Hydrothermal synthesis of hollow SnO2 spheres with excellent electrochemical performance for anodes in lithium ion batteries. (December 2017) - Liu, Ruiping; Su, Weiming; Shen, Chao; Iocozzia, James; Zhao, Shiqiang; Yuan, Kunjie; Zhang, Ning; Wang, Chang-an; Lin, Zhiqun
Graphical abstract: Highlights: Hollow SnO2 spheres were synthesized by NaF via employing hydrothermal method. The microstructure of hollow spheres can be judiciously controlled by adjusting the amount of NaF. Their high capacity reversibility and long-term cycling stability were demonstrated. Their excellent rate performance was also exhibited. Abstract: Hollow SnO2 spheres with oriented cone-like SnO2 nanoparticle shells were synthesized by a one-step hydrothermal process using NaF as the morphology controlling agent. The resulting hollow SnO2 sphere electrode exhibits high reversible capacity (initial charge and discharge capacities of 1342.9 and 1947.6 mAh/g at 0.1 C and 1235.4 and 1741.3 mAh/g at 1 C) and good cycling stability (discharge capacities maintained 758.1 and 449.6 mAh/g after 100 cycles at 0.1 C and 1 C, respectively). Good rate performance was also obtained (1234.5 mAh/g at 0.1 C, 884.2 mAh/g at 0.2 C, 692.4 mAh/g at 0.5 C, 497.6 mAh/g at 1 C, 315.8 mAh/g at 2 C and 80.6 mAh/g at 5 C, and more importantly, when the current density returns to 0.1 C, a capacity of 869.6 mAh/g can be recovered. The observed electrochemical performance can attributed to the hollow structure, the use of NaF for morphology control and the unique oriented cone-like shell of the particles.